Soil science education begins at an early age - Burbano O., Hernán (Revista de Ciencias Agrícolas, 2014)
This work analyzes education, its action, and importance; the need for soil science education at an early age; the developments in soil science education for children; and it presents a proposal in soil science education for Colombian children, in the framework of the Colombian Soil Science Society.